Cerebral amyloid angiopathy severity is linked to dilation of juxtacortical perivascular spaces. Issue 3 (March 2016) - van Veluw, Susanne J; Biessels, Geert Jan; Bouvy, Willem H; Spliet, Wim GM; Zwanenburg, Jaco JM; Luijten, Peter R; Macklin, Eric A; Rozemuller, Annemieke JM; Gurol, M Edip; Greenberg, Steven M; Viswanathan, Anand; Martinez-Ramirez, Sergi
Perivascular spaces are an emerging marker of small vessel disease. Perivascular spaces in the centrum semiovale have been associated with cerebral amyloid angiopathy. However, a direct topographical relationship between dilated perivascular spaces and cerebral amyloid angiopathy severity has not been established. We examined this association using post-mortem magnetic resonance imaging in five cases with evidence of cerebral amyloid angiopathy pathology. Juxtacortical perivascular spaces dilation was evaluated on T2 images and related to cerebral amyloid angiopathy severity in overlying cortical areas on 34 tissue sections stained for Amyloid β. Degree of perivascular spaces dilation was significantly associated with cerebral amyloid angiopathy severity (odds ratio = 3.3, 95% confidence interval 1.3–7.9, p = 0.011). Thus, dilated juxtacortical perivascular spaces are a promising neuroimaging marker of cerebral amyloid angiopathy severity.